PENERAPAN STRATEGI QUICK ON THE DRAW DALAM PEMBELAJARAN IPA SMP PADA MATERI SISTEM DALAM KEHIDUPAN MANUSIA - Atmah Atmah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Abstract: The teaching of the educational levels including at junior high school level is teacher-center learning, monotonous, rigid, and less interactive. Students are conditioned to be passive recipients, the impact students are less active, less passionate, loss of concentration, quickly bored, are not independent, even doing negative things. Problems are solved through the implementation of Strategy Quick on the Draw in Cooperative Learning. The purpose of the research is to improve students achievement in learning science especially on flat form material, students learning activities, and students response. The class action research conducts in 2 cycles. Each cycle consists of planning, acting, observing, evaluating and reflecting. The subjects are 27 students in the 9th grade class of SMPN 18 Banjarmasin. The result shows that (1) the teacher implemented lesson plan increases from 96.44% with good category in the first cycle to 100% with either category, (2) student learning activities in cycle 1 for positive activities 81 , 48% - 100%, which is not relevant to the behavior of 9.26% and in cycle 2 for positive activities 96.30 - 100%, which is not relevant to the behavior of 0%, (3) students understanding increases from 71.48 in the first cycle to 77.22 in the second cycle. As many as 92.59% students achieved ≥ 65% cognitive level (4) students response to positive learning activities.Key Words: Quick on The Draw, Cooperative Learning, Learning Outcome